2004
DOI: 10.1111/j.1365-2141.2004.05149.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐rich plasma serotonin levels in chronic myeloproliferative disorders: evaluation of diagnostic use and comparison with the neutrophil PRV‐1 assay

Abstract: Summary In a prospective study of 109 subjects, an enzyme‐linked immunosorbent assay (ELISA) was used to measure platelet‐rich plasma (PRP) serotonin levels in patients with polycythaemia vera (PV; n = 27), essential thrombocythaemia (ET; n = 14), myelofibrosis with myeloid metaplasia (MMM; n = 30), secondary or spurious polycythaemia (SP; n = 22) and controls (n = 16). Nine study subjects who were taking a selective serotonin reuptake inhibitor (SSRI) all displayed a markedly decreased PRP serotonin level (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 44 publications
0
12
0
1
Order By: Relevance
“…The authors identified PLT and increased intraplatelet serotonin levels among smokers and diabetic patients as possible contributors (7). In contrast to this, amongst patients with PV, PLT-rich plasma serotonin levels are decreased (29), which could be somehow explained by the efficiency of serotonin-reuptake-inhibitors (SSRI) in the treatment of some cases of PV-associated pruritus. Further research into the morphological parameters and their associations with pruritus could contribute to better understanding of the pathophysiology of AP and its management.…”
Section: Discussionmentioning
confidence: 97%
“…The authors identified PLT and increased intraplatelet serotonin levels among smokers and diabetic patients as possible contributors (7). In contrast to this, amongst patients with PV, PLT-rich plasma serotonin levels are decreased (29), which could be somehow explained by the efficiency of serotonin-reuptake-inhibitors (SSRI) in the treatment of some cases of PV-associated pruritus. Further research into the morphological parameters and their associations with pruritus could contribute to better understanding of the pathophysiology of AP and its management.…”
Section: Discussionmentioning
confidence: 97%
“…ET shares both bone marrow histological (dysmorphic megakaryocyte proliferation with clustering) and clinical (increased risk of thrombohaemorrhagic events) phenotype with PV (Michiels & Thiele, 2002;Elliott & Tefferi, 2005). Similarly, a substantial number of patients with ET display PV-characteristic biological features including clonal myelopoiesis (Fialkow et al, 1981), in vitro growth factor independence/hypersensitivity of both erythroid and megakaryocyte progenitor cells (Juvonen et al, 1993;Axelrad et al, 2000), low serum erythropoietin level (Messinezy et al, 2002), altered megakaryocyte/platelet Mpl expression (Harrison et al, 1999a;Yoon et al, 2000), increased neutrophil PRV-1 expression (Passamonti et al, 2004b;Tefferi et al, 2004a), and decreased platelet serotonin content (Koch et al, 2004). Furthermore, another shared molecular phenotype between ET, PV, and several other MPD has recently been reported and involves an activating JAK2 tyrosine kinase mutation (JAK2 V617F ) (Baxter et al, 2005;James et al, 2005; Summary Clinical correlates and long-term prognostic relevance of the JAK2 V617F mutation was studied in 150 patients with essential thrombocythaemia (ET) from a single institution and followed for a median of 11AE4 years.…”
mentioning
confidence: 99%
“…Accordingly, it is reasonable to speculate that qualitative or quantitative changes in platelet release products contribute to the pathogenesis of pruritus in PV. For example, platelet-rich plasma serotonin level is variably decreased in patients with PV [11] and PVassociated pruritus is sometimes controlled by treatment with selective serotonin reuptake inhibitors [3] Interesting in this regard is the fact that platelet abnormalities in smokers and diabetics include increased intraplatelet serotonin level [12,13], which is opposite to what is observed in PV [11]. Whether or not this explains the lower prevalence of pruritus in smokers or diabetics with PV requires a prospective examination accompanied by relevant laboratory correlative studies.…”
Section: Resultsmentioning
confidence: 99%